Clinical safety and efficacy of atosiban brief duration 14-hour treatment regimen in delaying preterm labor - Dewan, Bhupesh; Shinde, Siddheshwar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: For preventing preterm labor, the recommended duration of atosiban infusion is 48 hours and the patient has to be hospitalized during the course of treatment. The treatment consists of administering one vial of 0.9 ml as a bolus and then an infusion at a rate of 300 mcg/min for 3 hours followed by 100 mcg/min for the next 45 hours, utilizing nine vials of 5 ml. The objective of the study was to evaluate an alternative brief duration (14-hour) of atosiban treatment involving a bolus dose of 0.9 ml followed by an infusion of 300 mcg/min for 2 hours and 100 mcg/min for the next 12 hours utilizing 3 vials of 5 ml. The advantage being that the treatment could be completed in an outpatient setup and be convenient for the patient as well as for the healthcare staff. This would also reduce the overall cost of the treatment. This prospective single-center study was conducted to evaluate the efficacy and safety of an atosiban brief duration (14-hour) treatment regimen to prevent preterm labor. Methods: A total of 50 patients with symptoms of preterm labor were enrolled in the study. The efficacy of tocolysis was determined by the percentage of patients who remained undelivered up to 48 hours after atosiban therapy initiation and the follow-up of the patients was done up to delivery. Safety was assessed in terms of the number of maternal and fetal adverse events reported. Results: The mean gestational age at the enrolment was 32.1±2.6 weeks and the delivery were delayed by a mean of 18.13±17.97 days (range 1-62 days). Thirty-five (70%) patients remained undelivered at 48 hours and 29 (58%) at 7 days. No maternal or fetal adverse events were reported during the study. Conclusions: A favourable safety and efficacy profile of a brief duration atosiban regimen was observed resulting in ease of administration and a shorter stay in the healthcare facility providing convenience to both patient and hospital staff. The overall cost of the therapy was also reduced. Further clinical trials with larger sample size are required to confirm the findings.